3D-Printed Flat-Bone-Mimetic Bioceramic Scaffolds for Cranial Restoration - Zhang, Yihang; He, Fupo; Zhang, Qiang; Lu, Haotian; Yan, Shengtao; Shi, Xuetao (Research (Washington), 2023)
The limitations of autologous bone grafts necessitate the development of advanced biomimetic biomaterials for efficient cranial defect restoration. The cranial bones are typical flat bones with sandwich structures, consisting of a diploe in the middle region and 2 outer compact tables. In this study, we originally developed 2 types of flat-bone-mimetic β-tricalcium phosphate bioceramic scaffolds (Gyr-Comp and Gyr-Tub) by high-precision vat-photopolymerization-based 3-dimensional printing. Both scaffolds had 2 outer layers and an inner layer with gyroid pores mimicking the diploe structure. The outer layers of Gyr-Comp scaffolds simulated the low porosity of outer tables, while those of Gyr-Tub scaffolds mimicked the tubular pore structure in the tables of flat bones. The Gyr-Comp and Gyr-Tub scaffolds possessed higher compressive strength and noticeably promoted in vitro cell proliferation, osteogenic differentiation, and angiogenic activities compared with conventional scaffolds with cross-hatch structures. After implantation into rabbit cranial defects for 12 weeks, Gyr-Tub achieved the best repairing effects by accelerating the generation of bone tissues and blood vessels. This work provides an advanced strategy to prepare biomimetic biomaterials that fit the structural and functional needs of efficacious bone regeneration.